Meningkatkan Aktivitas dan Hasil Belajar Siswa IPAS Dengan Model Pembelajaran Project Based Learning (PJBL) Pada Kelas IV SD 02 Ujung Gunung Ilir Tahun pelajaran 2023/2024 - Sella Septia; Dina Syaflita (Kilau Publishing, 2024)
The research is based on the low activity and learning outcomes of students in class IV SDN 02 Ujung Ilir. This study aims to improve the activity and learning outcomes of students in science learning with the Project Based Learning (PjBL) model in class IV SDN 02 Ujung Ilir. The research is an action in the classroom. The subjects of the study were 30 students in class IV SDN 02 Ujung Ilir in the odd semester of 2023/2024. The procedure of the study began with planning, implementation, observation, and reflection. The study produced instructions in cycle I for making learning modules, the average percentage was 82.91% (B), in cycle II there was an increase of 90.68% (SB). Second, the results of the implementation of the learning aspects of teachers in cycle I obtained an average of 75% (C), in cycle II there was an increase to 92.75% (SB). Third, the results obtained from the application of student learning aspects in cycle I averaged 77.22% (C), in cycle II there was an increase to 92.65% (SB). Fourth, the results of student learning in cycle I obtained an average of 78.08 (C), in cycle II there was an increase to 84.67 (B). So it can be concluded that the PJBL Model can improve student activity and learning outcomes in science learning in class IVSD 02 Ujung Gunung Ilir.